Ultra-Fast ASP.NET 4.5 - Kiessig, Rick (Apress : Imprint: Apress, 2012)
Ultra-Fast ASP.NET 4.5 presents a practical approach to building fast and scalable web sites using ASP.NET and SQL Server. In addition to a wealth of tips, tricks and secrets, you'll find advice and code examples for all tiers of your application, including the client, caching, IIS 7.5, ASP.NET 4.5, threads, session state, SQL Server 2012 (otherwise known as Denali), Analysis Services, infrastructure and operations. By applying author Rick Kiessig's ultra-fast approach to your projects, you'll squeeze every last ounce of performance out of your code and infrastructure-giving your site unrivaled speed. Rather than drowning you in options, Ultra-Fast ASP.NET 4.5 presents and explains specific high-impact recommendations and demonstrates them with detailed examples. Using this knowledge, you will soon be building high-performance web sites that scale easily as your site grows. Apply the key principles that will help you build Ultra-Fast and Ultra-Scalable web sites. Identify performance traps (such as with session state) and learn how to avoid them. Put into practice an end-to-end systems-based approach to web site performance and scalability, which includes everything from the browser and the network to caching, back-end operations, hardware infrastructure, and your software development process.